Roles and therapeutic potential of CD1d-Restricted NKT cells in inflammatory skin diseases - Lee, Sung Won; Park, Hyun Jung; Van Kaer, Luc; Hong, Seokmann (Frontiers in Immunology, 2022)
Natural killer T (NKT) cells are innate-like T lymphocytes that recognize glycolipid antigens rather than peptides. Due to their immunoregulatory properties, extensive work has been done to elucidate the immune functions of NKT cells in various immune contexts such as autoimmunity for more than two decades. In addition, as research on barrier immunity such as the mucosa-associated lymphoid tissue has flourished in recent years, the role of NKT cells to immunity in the skin has attracted substantial attention. Here, we review the contributions of NKT cells to regulating skin inflammation and discuss the factors that can modulate the functions of NKT cells in inflammatory skin diseases such as atopic dermatitis. This mini-review article will mainly focus on CD1d-dependent NKT cells and their therapeutic potential in skin-related immune diseases.